Survive or suffer: sustainability of addiction care curriculum/training in South African Universities. - Harker, Nadine; Weich, Lize; Sibeko, Goodman; Ashburner, Fergus; Allie, Shaheema; Kader, Rehana (Journal of Substance Use, 2025)
South Africa is grappling with a significant challenge of high harmful substance use rates, a shortage of addiction care professionals, and an expanding treatment gap. In response, the Department of the Premier initiated a project in 2010 to revamp its approach to substance use treatment in the Western Cape. This endeavor led to the establishment of a postgraduate diploma in addictions (PGDIP) in collaboration with the Universities of Cape Town and Stellenbosch. The PGDIP aimed to enhance the expertise of healthcare professionals in evidence-based practices for substance use prevention and treatment. Despite the initial success of the program in upskilling professionals and improving addiction care quality, financial constraints threaten its continuity, hindering the upskilling of the addiction treatment workforce. The cessation of bursaries and the self-funding requirements pose challenges to training professionals in evidence-based approaches. The growing prevalence of substance use disorders in South Africa underscores the urgency of investing in addiction specialists to address the escalating demand for treatment services and the complex needs of individuals struggling with addiction. To avert a potential public health crisis, it is imperative for the country to prioritize the training of addiction practitioners and ensure standardized academic training to professionalize the addiction workforce. Significance: South Africa is grappling with high rates of substance use, a shortage of addiction professionals, and an expanding treatment gap. In 2010, the Western Cape government initiated a project to revamp its approach to substance use treatment. This endeavor led to the establishment of a postgraduate diploma in addictions (PGDIP) at two Universities. The PGDIP aimed to enhance the expertise of healthcare professionals. Despite the initial success of the course, it now faces discontinuation. The growing prevalence of substance use disorders underscores the urgency of investing in addiction specialists. It is imperative the country prioritizes the training of addiction specialists.